2011
DOI: 10.1021/jm200410r
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of an Important Drug Lead Podophyllotoxin Can Be Efficiently Mimicked by Diverse Heterocyclic Scaffolds Accessible via One-Step Synthesis

Abstract: Structural simplification of an antimitotic natural product podophyllotoxin with mimetic heterocyclic scaffolds constructed using multicomponent reactions led to the identification of compounds exhibiting low nanomolar antiproliferative and apoptosis-inducing properties. The most potent compounds were found in the dihydropyridopyrazole, dihydropyridonaphthalene, dihydropyridoindole and dihydropyridopyrimidine scaffold series. Biochemical mechanistic studies performed with dihydropyridopyrazole compounds showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…5A-C). Mechanistic studies revealed that DMEP could disrupt microtubule organization and inhibit the formation of mitotic spindles which lead to G2/M phase arrest [43]. VP-16 was proven to inhibit DNA topoisomerase II by stabilizing the DNA-enzyme complex during DNA replication which led to S and G2 phase arrest with the inhibition of DNA synthesis [44].…”
Section: Discussionmentioning
confidence: 99%
“…5A-C). Mechanistic studies revealed that DMEP could disrupt microtubule organization and inhibit the formation of mitotic spindles which lead to G2/M phase arrest [43]. VP-16 was proven to inhibit DNA topoisomerase II by stabilizing the DNA-enzyme complex during DNA replication which led to S and G2 phase arrest with the inhibition of DNA synthesis [44].…”
Section: Discussionmentioning
confidence: 99%
“…(Magedov et al , 2007) More recently, the replacement of methylenedioxybenzene subunit with a pyrazole moiety yielded the second-generation tetracyclic dihydropyridopyrazoles (DPPs) with enhanced nano-molar potencies. (Magedov et al , 2011) It was shown that DPPs exerted anticancer effects by disrupting microtubule dynamics in cancer cells through binding to the colchicine site of β-tubulin. However, despite their nanomolar antiproliferative potencies and potential advantages commonly associated with the “colchinoids,” such as the ability to act as selective vascular disrupting agents and overcome the efflux pump/mutant tubulin/class III β-tubulin overexpression-mediated multidrug resistance, (Lu, 2012) further development of these agents was hampered due to poor water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydropyridopyrazoles XIII were obtained when furan-2,4-dione XI was used as CH-acid in the reaction with salicylaldehydes X and 5-aminopyrazole XII in ethanol with catalytic amounts of Et 3 N. 12 In this case the hydroxyl group of the salicylaldehyde was not involved in the reaction (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%